Crossing the chest: bandoliers with and without bullets in imaging the ’Zulu’ - Nettleton, A. (Southern African Humanities, 2017)
Beaded bandoliers have been part of a repertoire of dress used by isiZulu speakers for 200 years. In this paper, I trace the emergence of a particular form of bandolier and speculate on the links between their indigenous use and their particular military associations among the colonists. At the centre of this research is an image of isiZulu-speaking (and other) troops drawn from the Natal Colony in the Anglo-Zulu War of 1879, in which the black troops are shown wearing bullet-stocked bandoliers and waving guns while cheering Lord Chelmsford. In parsing the visual representation of isiZulu speakers in the Illustrated London News coverage of the war, I have attempted to show how indigenous understandings of the bandolier enabled a particular form of assimilation of flat, beaded bandoliers into ‘Zulu’ dress practice. I trace their evolution from items primarily made as protective gear to fashion statements. The paper concludes with an examination of mid-20th-century images of bandolier usage in the Nongoma district of Zululand and a consideration of particular design types.